The Sovereignty Deficit of Modern Constitutions - Galligan, D (2013)
The aim of this essay is to examine the place of the people in the constitutions of democratic nations. While the meaning of democracy and the degree to which it is achieved vary within the family of nations considered democratic, the idea common to all is that the people are self-governing. In its origins, the idea is tied to liberty: not to be self-governing is to be subject to the will of another and so not to be free. What constitutes self-government is open to interpretation, although this is not the place to examine the possible meanings. Nor is this the place to set out the history of the idea or to show how it became central to modern constitutions, except to note the number of nations qualifying as democratic has steadily increased in recent years to just under a half of the total. It seems reasonable to assume that a democratic nation, a self-governing people, would want to make sure that the constitution, the basic of government and of relations between the people and government, provide for and protect self-government and hence democracy. © The Author 2013.